Determinants of the influence for information technology on SMEs in Medan city - Magdalena Judika Siringoringo; Hendrik E. Samosir; Pedro Siringoringo; Roy Alfonso E. Sinaga; Ignatius Valdo Silalahi (Jurnal Mantik, 2023)
Small and medium enterprises (hereinafter shortened to SMEs) encourage economic development by creating jobs. Based on data from the Bureau of Statistics (BPS), medium-scale businesses (0.14% of total businesses) with a capital value of between 1 billion and IDR 50 billion are only able to absorb 10.83% of the workforce. Medium-sized businesses are under great pressure to achieve competitive advantage and improve operational and logistics performance. At the same time, SMEs are required to submit to demand uncertainty and market volatility so as to survive in this market. Information technology support allows management to make business decisions quickly and accurately. The main problem for SMEs in the technology adoption process is that IT adoption by medium-sized businesses in Indonesia is still very low. SMEs have not adopted much IT because the need for IT in their business processes has not yet emerged and they lack financial support for this. In Indonesia, some SMEs run their businesses using traditional methods. Even though currently companies compete through sophisticated technology and IT to be able to win the competition.